2018
DOI: 10.3389/fimmu.2018.01223
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Impairment Is Associated With Increased Inflammasome Activation and Reversal Reaction Development in Multibacillary Leprosy

Abstract: Leprosy reactions are responsible for incapacities in leprosy and represent the major cause of permanent neuropathy. The identification of biomarkers able to identify patients more prone to develop reaction could contribute to adequate clinical management and the prevention of disability. Reversal reaction may occur in unstable borderline patients and also in lepromatous patients. To identify biomarker signature profiles related with the reversal reaction onset, multibacillary patients were recruited and class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Increased bright specks of NLRP3 and IL-1β detected in the lung of βENaC overexpressing mice were highly localized to the vicinity of mucus plaques and plugs. Specks vs. homogenous fluorescence reflects oligomeric vs. monomeric states and is a method for the detection of NLRP3 inflammasome activation [21]. In the lungs, measurement of IL-1β/ IL-18 in BAL is a commonly accepted technique to detect inflammasome activation, particularly in mouse studies [22].…”
Section: Discussionmentioning
confidence: 99%
“…Increased bright specks of NLRP3 and IL-1β detected in the lung of βENaC overexpressing mice were highly localized to the vicinity of mucus plaques and plugs. Specks vs. homogenous fluorescence reflects oligomeric vs. monomeric states and is a method for the detection of NLRP3 inflammasome activation [21]. In the lungs, measurement of IL-1β/ IL-18 in BAL is a commonly accepted technique to detect inflammasome activation, particularly in mouse studies [22].…”
Section: Discussionmentioning
confidence: 99%
“…Even more, autophagy was also suggested to play an important role in T1R in multibacillary leprosy. In a study of multibacillary leprosy (BL and LL), the researchers found that autophagy was downregulated in patients who developed T1R in the future compared to patients who did not develop T1R (20). And the authors also demonstrated a significantly higher level of IL-1β in the serum of T1R group months before T1R onset, suggesting IL-1β as a potential marker for T1R prediction (20).…”
Section: Macrophagesmentioning
confidence: 96%
“…As observed in Figures 1B,C Previous work from our group has demonstrated the presence of different tissue macrophage phenotypes in skin from paucibacillary and multibacillary leprosy patients. Whereas, proinflammatory markers were more expressed in paucibacillary, anti-inflammatory and scavenger receptor expressions were higher in samples from the multibacillary patients (6). In order to investigate the cell phenotypes present in lesions from leprosy-HIV co-infected patients, with or without RR, we evaluated pro-, and anti-inflammatory macrophage markers (pro-inflammatory: IL12B, IL23A, IL1B, CXCL10; and anti-inflammatory: VEGF, ARG2, PPARG, PDGFA, CD163, MRS1) as well as markers that could be present in both macrophage phenotypes, depending on the environment (IDO, HMOX1, CD209).…”
Section: Monocyte Phenotype In Co-infected Rr/hiv Patientsmentioning
confidence: 83%
“…In contrast, skin cells from multibacillary patients are highly phagocytic and have a suppressive phenotype marked by an increase of alternatively activated macrophage markers, CD163 and macrophage scavenger receptor 1 (MRS1) (3,5). The macrophage phenotype that predominates in multibacillary patients contributes to bacterial survival and persistence inside cells by an IL-10-mediated pathway (2,6).…”
Section: Introductionmentioning
confidence: 99%